Three decades of Malay linguistics research: a scientometric analysis of trends, impact, and emerging directions - Lalu Nurul Yaqin; Yabit Alas; Salinah Ja’afar (Penerbit Universiti Kebangsaan Malaysia, 2025)
The study presents a scientometric analysis of the development of Malay linguistics research over the past three decades. Due to rapid technological changes in linguistics and policy needs, this study examines publication trends, institution and country contributions, themes, and co-citation cluster networks to provide an overview of the field's intellectual structure. The study utilises CiteSpace version 6.3. R3 Advance to analyse records from the Scopus database (1994-2024). The findings indicate substantial growth in publication output, with Malaysia publishing the most papers, followed by Indonesia, Australia, Singapore, and Brunei Darussalam. Universiti Kebangsaan Malaysia, Universiti Sains Malaysia, Universiti Malaya, Universiti Putra Malaysia, Universiti Teknologi Mara, and International Islamic University of Malaysia are the top contributing institutions to research in Malay linguistics. The emerging themes indicate a shift in research focus from traditional linguistic studies toward computational linguistics, digital text processing, and AI-driven applications. The key research clusters were identified, spanning dialectology, historical linguistics, sociolinguistics, and computational linguistics. Among influential contributors, Asmah Haji Omar, with a citation count of 55 and burstness of 4.08, is the most influential author, significantly shaping the discipline. The GEMA Online Journal of Language Studies has the highest citation bursts (1.81), which are crucial in advancing research in computational linguistics, sociolinguistics, and language identity. This study provides critical insights into the evolution of Malay linguistics research, offering valuable evidence to guide researchers and education policymakers in formulating strategic policies for academic innovation and disciplinary advancement.